Quantum Cryptography, Quantum Communicatıon and Quantum Computing Problems and Solutions - Gençoğlu, Muharrem Tuncay (My University, 2021)
The development of quantum technologies will open up new perspectives in the use of quantum algorithms, the creation and modeling of complex physical and biological systems, new physical methods of transmitting, receiving and processing information. In turn, this will give impetus to the development of a large number of applications in the scientific, technical, economic and social spheres of society. Quantum cryptography is a communication protection method based on certain phenomena of quantum physics. Unlike traditional cryptography, which uses mathematical methods to ensure the secrecy of information, quantum cryptography focuses on physics, where information is carried using objects of quantum mechanics. The process of sending and receiving is always carried out by physical means, for example using electrons in an electric current, or photons in fiber-optic communication lines. In this process, the current situation was determined and the problems encountered and the solution suggestions for these problems were tried to be addressed.
Keywords: Quantum cryptography; quantum communication; quantum computing; quantum problems